Petrologia e geocronologia do batólito Rio Jacaré, domínio Poço Redondo, sistema orogênico sergipano - Sousa, Carlos Santana (2018)
The Rio Jacaré Batholith (RJB, 167 km²), southern part of the Poço Redondo Domain, Sergipano Orogenic System, is an intrusion with frequent magmatic foliation and no deformation is observed. The rocks of the RJB have compositions monzogranitic, granodioritic and monzonite quartz, gray color, medium to gross granulation with inequigranular and porphyritic textures. Microgranular mafic enclaves are abundant, have dioritic and granodioritic compositions, and preserve mingling and mixing features. They have dark gray color, sizes up to 2 m and fine granulation. RJB rocks and their enclaves have similar mineralogy. The mafic minerals are biotite, hornblende and iron-titanium oxides. The plagioclases (andesine and oligoclase) exhibit compositional zoning, dominantly normal, suggesting existence of magmatic fractionation. The alkaline feldspar (orthoclase and microcline) has composition of Or75-98-Ab25-2. The biotite (0.3 <Fe / (Fe + Mg) <0.6) is magmatic and requilibrated. The magmatic Mghornblende and edenite crystallized under conditions of high fO2, the maximum depth of 25 km and temperature of 826.3 °C. The geochemical data show that RJB rocks are magnesian, metaluminous and belong to the calc-alkaline of high K and alkali-calcic series and that their enclaves are shoshonitics. The [La/Yb]N (13-133) and negative Eu anomalies show a high degree of fractionation. The RJB is ediacaran and has UPbSHRIMP 617 ± 4 Ma cristalization age. The low contents of Ta, Nb, Ti and P, and moderates of Y, Nb and Rb of the rocks indicate magmas generated in orogenic and post-collisional environment.